2021
DOI: 10.1097/wad.0000000000000420
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Orchestrates Factor XII and Platelet Activation Leading to Endothelial Dysfunction and Abnormal Fibrinolysis in Alzheimer Disease

Abstract: Alzheimer disease (AD) is the most common form of dementia in humans. However, to date, the cause of sporadic AD (SAD), which is the most frequent form, is still unknown. Although it has not been possible to determine the origin of this disease, the amyloid hypothesis is one of the most accepted to explain the etiology of AD. This hypothesis proposes that the pathogenesis of AD is derived from the toxic effect produced by the amyloid-β (Aβ) peptide in the brain parenchyma, but it does not make clear how Aβ is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Increased thrombin activity can lead to blood-brain barrier disruption, allowing the entry of blood components, including fibrinogen, where amyloid-beta (Aβ) is abundant. Therefore, this Aβ interacts with fibrinogen, which favors the formation of blood clots resistant to fibrinolysis, which can contribute to the development and progression of AD pathology [39,40]. Upregulation of PAI-1 has also been shown in PD and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Increased thrombin activity can lead to blood-brain barrier disruption, allowing the entry of blood components, including fibrinogen, where amyloid-beta (Aβ) is abundant. Therefore, this Aβ interacts with fibrinogen, which favors the formation of blood clots resistant to fibrinolysis, which can contribute to the development and progression of AD pathology [39,40]. Upregulation of PAI-1 has also been shown in PD and AD.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with primary endothelial cells from isolated blood vessels and human microvessels have shown that patient-derived Aβ binds to Na + /K + -ATPase α3 subunit (NAKα3) in endothelial cell vesicles to inhibit vasodilation ( Sasahara et al, 2021 ). By activating factor XII (FXII) and interacting with fibrinogen, Aβ may support inflammatory and thrombogenic processes ( García-Mejía et al, 2021 ). Through the intrinsic clotting pathway, Aβ causes FXI activation, the production of thrombin and fibrin.…”
Section: Aβ and Neurovascular Dysfunction: Causality Or Causative Int...mentioning
confidence: 99%